Effect of Knowledge Attitudes of Vulva Hygiene Behavior in Female Adolescent at SMAN 1 Sukakarya Bekasi Period February 2022 - Mita Miftahul Jannah; Maryati Sutarno (Institute of Computer Science (IOCS), 2022)
Lack of knowledge and information regarding the health of reproductive organs is the cause of the growth of microorganisms that interfere with the function of the reproductive organs. The results of the preliminary study between SMAN 1 SUKAKARYA and SMAN 1 SUKATANI, it was found that the knowledge of students about vulva hygiene behavior was 30% less than that of students at SMAN 1 SUKATANI by 70%. The purpose of this study was to determine the effect of knowledge and attitudes on vulva hygiene behavior in adolescent girls at SMAN 1 Sukakarya, Bekasi Regency period 2022. This method used in this study used a cross sectional research design. The sampling technique used is accidental sampling with a sample of 67 respondent. The results of the analysis using the chi square test and the p-value is greater than α = 0.05, so there is no relationship between the knowledge and attitudes of young women with vulva hygiene behavior at SMA Negeri 1 Sukakarya, Bekasi Regency period 2022.